The Role of Green Productivity to Success the industrial organizations Applied Study in Midland Refineries Company – Al Daura Refinery - داود فضيلة سلمان; كرم حامد عبد الرضا (Journal of Economics and Administrative Sciences, 2015)
The Green Productivity topic is considered as one of the more conceptual novelty in the field of Production and Operations Management, and one of the least topics addressed in the literature competent, Green Productivity (GP) is a strategy for enhancing a business’s Productivity and environmental performance at the same time, for overall socio - economic development, It is the application of appropriate techniques , technologies , and management systems to produce environmentally compatible goods and services. the research aimed to find the contribution of this concept for success the industrial Organizations. The search adopted to calculate the environmental impact of refining the crude oil, productivity, indicators for green productivity there are "Green productivity Index, Green productivity Ratio" as elements of the independent variable "green productivity" also calculate (efficiency and effectiveness) as elements of the dependent variable, "the success of industrial organizations", and adopted the calculations once the current situation, and again assuming the development of alternative situation that by application a modern technique (RFCC) to production of oil derivatives from fuel oil, in addition to the assumption of the existence an industrial Holocaust for solid waste, and statement impact of these alternatives on each of the elements of the two variables independent and affiliated then find the relationship between them. And research has come to positive results, such as reducing the volume of solid and gas waste, which in turn led to reducing the environmental impact of the basic, increased productivity, and high green productivity index, as well as the positive ratio of green productivity, on the other hand noted the high level of efficiency and effectiveness This is indicated preference by the situation alternative to the current situation,this means the application of green productivity contributes to the successful of industrial organizations.